Associations between external eating cues, diet history and weight history in French subjects with obesity - Ducy, Emilie; Romon, Monique; Amouyel, Philippe; Meirhaeghe, Aline (Appetite, 2025)
Obesity remains a serious public health concern. Historically, restrictive diets were the first line of treatment for obesity and are still frequently followed by subjects with obesity. However, some studies showed that dieting may contribute to long-term weight gain. External eating cues might be implicated in this deleterious effect. We then wanted to determine whether the history of dieting was associated with higher reliance on external eating cues (such as emotional eating, uncontrolled eating, or ending a food intake because of the stomach overfullness or the plate emptiness) in individuals with obesity, and to examine whether these associations differed between subjects with different weight history. We included 1093 subjects with obesity from the GECCOS study and examined the association between external eating cues and dieting history (if < 3 diets or ≥ 3 diets) in the sample and in clusters (defined by hierarchical ascending classification on their weight history (based on current BMI, BMI at 20 years old and age of 1st diet)). Three clusters were obtained: a “early-onset obesity” group, a “late-onset obesity” group and an “intermediate” group. Having followed at least 3 diets was associated with higher BMI, higher emotional eating and with eating until stomach overfullness in the global population, but it was not associated with uncontrolled eating or for ending the meal when the plate is empty. These associations were not always detected in each cluster, showing that weight history modulated these associations. To conclude, dieting history is associated with certain external eating cues such as emotional eating and stopping the meal at stomach overfullness in subjects with obesity, even when their weight history is taken into account.